Digital fabrications : architectural and material techniques - Iwamoto, Lisa, 1963- (New York : Princeton Architectural Press, 2009)
Introduction ;##Sectioning : Digital weave / University of California, Berkeley, Lisa Iwamoto ; Mafoombey / Martti Kalliala / Esa Ruskeepää / Martin Lukasczyk ; (Ply)wood delaminations / Georgia Institute of Technology, Monica Ponce de Leon ; A change of state / Georgia Institute of Technology, Nadar Tehrani ; [c]space / Alan Dempsey and Alvin Huang ; BURST*003 / SYSTEMarchitects -- ## ##Tessellating : West Coast Pavilion / Atelier Manferdini ; Huyghe + LeCorbusier Puppet Theater / MOS ; Helios House / Office dA and Johnston Marklee & Associates ; California: stage set for John Jasperse / AEDS/Ammar Eloueini ; Airspace: Tokyo / Thom Faulders Architecture ; Technicolor bloom / Brennan Buck -- ## ##Folding : Dragonfly / Tom Wiscombe/EMERGENT ; Nubik / AEDS/Ammar Eloueini ; In-out curtain / IwamotoScott ; Entry Paradise Pavilion / Chris Bosse/PTW Architects ; Aoba-tei / Atelier Hitoshi Abe ; Digital origami / University of Technology, Sydney, Chris Bosse ; C_Wall ; Manifold / Andrew Kudless/Matsys -- ## ##Contouring : Bone wall / Urban A+O ; Design 306 / Erwin Hauer and Enrique Rosado ; CNC panels / Jeremy Ficca ; Door with peephole / Williamson Williamson ; Gradient scale / SPAN ; Tool-hide / Ruy Klein -- ## ##Forming : Alice / Florencia Pita mod ; Prototype pavilion / MOS ; UniBodies / PATTERNS, with Kreysler & Associates ; NGTV / GNUFORM ; "Dark places" / servo ; Housing in Vienna / SPAN ; Satin sheet ; Shiatsu / University of California, Los Angeles, Heather Roberge ; P_Wall / Andrew Kudless/Matsys.
Includes bibliographical references (p. 140).
boek
Keywords: Iwamoto, Lisa